What works to improve the quality of student learning in developing countries? - Serena Masino; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We conducted a systematic review to identify policy interventions that improve education quality and student learning in developing countries. Relying on a theory of change typology, we highlight three main drivers of change of education quality: first, supply-side capability interventions that operate through the provision of physical and human resources, and learning materials; second, policies that through incentives seek to change both teachers, household and student behaviour and intertemporal preferences; and third, bottom-up and topdown participatory and community management interventions, which operate through decentralization reforms and knowledge diffusion and increased community participation in the management of education systems. Overall, our findings suggest that policy interventions are more effective in improving student performance and learning when two or more drivers of change are combined. Supply-side interventions are more effective when they are complemented with community participation and/or incentives. Thus, idiosyncrasies, social norms and intertemporal preferences need to be factored in when designing education policies in developing countries.
Keywords: I25; I28; I38; C10; O50; 330; education quality; student learning; education policy; developing countries; systematic review